EP033/#52 A qualitative exploration of perceived causes of breast cancer in Busia and Trans Nzoia, Western Kenya. (4th December 2022) - Mujumdar, Vaidehi; Naanyu, Violet; Kamano, Jemima; Cherono, Phoebe; Koros, Hilary; Etyang, Lennah; Misoi, Lawrence; Itsura, Peter; Tonui, Philliph; Ejersa, Waqo; Schneidman, Miriam; Aruasa, William
Abstract : Objectives: The Primary Integrated Care for Four Chronic Diseases (PIC4C) is an initiative by the Kenyan Ministry of Health and Moi Teaching Hospital to pilot screening, referral, treatment integration for diabetes, hypertension, breast cancer, cervical cancer in Busia and Trans-Nzoia, Western Kenya. A major aspect of the PIC4C qualitative arm was to determine how localized knowledge affects perceptions of breast cancer causes in the two counties and to use this information to develop targeted interventions. Methods: 174 participants were included in 18 focus group discussions (FGDs) engaging patients, community members (CHVs), health care providers (HCPs). 12 patients with breast cancer were included in patient FGDs. The group sessions were facilitated by trained moderators and captured using audio recorders and field notes. Two analysts independently coded and analyzed the data using NVivo 12. Results: Overall, patients, CHVs, HCPs perceived breast cancer to be a chronic disease that could be treated, but led to death. All participants perceived genetics, unhealthy eating, low breastfeeding rate to cause breast cancer. Three factors were reported by patients and community members, but not by HCPs: poor breast hygiene, poorly fitting bras, witchcraft. Only HCPs cited smoking as a cause of breast cancer. Conclusions: This study reports how localized knowledge affects perceptions of breast cancer causes in Busia and Trans-Nzoia. Our study shows that misconceptions and inadequate knowledge about breast cancer causes persist in the two counties. Our findings suggest a need for improved screening and treatment via dedicated health education campaigns, treatment resources, training for CHVs and HCPs to ensure communities receive accurate information.